How to make two-lane rural roads safer scientific background and guide for practical application - Lamm, Ruediger; Beck, A.; Ruscher, T.; Mailaender, T. (WIT Press, 2007)
Describes a methodology which supports the achievement of quantified measures of design consistency, operating speed consistency, and driving dynamic consistency of two lane rural roads. This book provides an overview of the safety evaluation process. It is useful for educators, students, consultants, highway engineers, and scientists.